Analisa Terapan Teknologi Pengeringan Higienis pada Cabai Rawit Kering untuk Stabilitas Pasokan di Luar Panen Raya - Farahdiansari, Ardana Putri; Surya Effendi, Meilisa Rusdiana; Stighfarrinata, Rizky; Maghfiroh, Amalia Ma'rifatul (Institut Teknologi Adhi Tama Surabaya, 2025)
This study aims to analyze the application of hygienic design to utilize the excess supply of cayenne pepper during the peak harvest season, where many harvests are not absorbed into the market. Meanwhile, during the harvest in the off-season, the amount of chili harvest is unable to meet market demand, resulting in a spike in the price of cayenne pepper. The spike in the price of cayenne pepper has quite high variability, where the lowest price is IDR 15,000.00 but the highest price can reach IDR 100,000.00. With the implementation of the use of the DrySter Eco House drying house, farmers can store excess harvest results when prices drop and process them as dried cayenne pepper supplies and then sell them when the supply of fresh cayenne pepper on the market is low and the selling price is high. The DrySter Eco House greenhouse system relies on solar energy as the main source. This approach utilizes a greenhouse structure equipped with temperature and humidity control technology, as well as air circulation assistance that utilizes energy from solar panels to maintain optimal conditions during the drying process. By using greenhouse technology, the water content of cayenne pepper can be reduced significantly in a shorter time compared to conventional open drying methods. The use of renewable energy not only reduces operational costs, but also supports environmental sustainability and is able to maintain the quality of dried cayenne pepper. This study includes trials and measurements of several variables, such as temperature and drying time, to compare the results of conventional drying with drying using the DrySter Eco House prototype. With the supply of cayenne pepper from prospective harvest waste, farmers can stabilize the supply of chili during the off-season while also obtaining additional income from the sale of dried chili.